Developing A Family-Size Biogas-Fueled Electricity Generating System - Agus Haryanto; Fadli Marotin; Sugeng Triyono; Udin Hasanudin (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
The purpose of this study is to develop a family-size biogas-fueled electricity generating system consisting of anaerobic digester, bio-filter scrubber, and power generating engine. Biogas was produced from a pilot scale wet anaerobic digester (5-m3 capacity). The biogas was filtered using bio-scrubber column filled with locally made compost to reduce hydrogen sulfide (H2S) content. Biogas composition was analysed using a gas chromatograph and its H2S level was measured using a H2S detector. A 750-W four stroke power generating engine was used with 100% biogas. Biogas consumed by the generator engine was measured at different load from 100 to 700 W (13.3 to 93.3% of the rated power). Three replications for each load experiment were taken. Results showed that the total biogas yield was 1.91 m3/day with methane content of 56.48% by volume. Bio-filter successfully reduced H2S content in the biogas by 98% (from 400 ppm to 9 ppm). Generator engine showed good performance during the test with average biogas consumption of 415.3 L/h. Specific biogas consumption decreased from 5.05 L/Wh to 1.15 L/Wh at loads of 100 W to 700 W, respectively. Thermal efficiency increased with loads from 6.4% at 100 W to 28.1 at 700 W. The highest thermal efficiency of 30% was achieved at a load of 600 W (80% of the rated power) with specific biogas consumption of 1.07 L/Wh.Article History: Received Janury 16th 2017; Received in revised form 2nd June 2017; Accepted 18th June 2017; Available onlineHow to Cite This Article: Haryanto, A., Marotin, F., Triyono, S., Hasanudin, U. (2017), Developing A Family-Size Biogas-Fueled Electricity Generating System. International Journal of Renewable Energy Development, 6(2), 111-118.https://doi.org/10.14710/ijred.6.2.111-118